Right to Privacy, Constitutional Rights and latest reform in 2017 - Singla, Manu (Innovative Research Thoughts, 2017)
The right to privacy refers concept that someone's particular information is protected from public scrutiny. U.S. Justice Louis Brande’s called it "the right to leave alone". Although not explicitly stated in the American Constitution, some amendments provide the some protection. The right to privacy is often secured by statutory law. For ex., The Health Information Portability & Accountability Act protects a person's health information, & the Federal Trade Commission implements the right to privacy in various privacy statements & privacy policies. The rights to privacy should often be equalized against the state attractive interests, including encouraging public safety & improving the quality of life. Motorcycle helmet & Seat belt laws requirements are ex. of such laws & while many Americans have enough information that the government saves personal information, mostly says that government surveillance is tolerable.